2006
DOI: 10.1371/journal.pbio.0040369
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of PGC-1β Results in Defective Mitochondrial Activity, Thermogenesis, Hepatic Function, and Cardiac Performance

Abstract: The transcriptional coactivator peroxisome proliferator-activated receptor-gamma coactivator-1β (PGC-1β) has been implicated in important metabolic processes. A mouse lacking PGC-1β (PGC1βKO) was generated and phenotyped using physiological, molecular, and bioinformatic approaches. PGC1βKO mice are generally viable and metabolically healthy. Using systems biology, we identified a general defect in the expression of genes involved in mitochondrial function and, specifically, the electron transport chain. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
240
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(263 citation statements)
references
References 36 publications
18
240
4
Order By: Relevance
“…Similar data have been reported from cultures of brown adipocytes isolated from whole-body PGC-1α knockout mice (39). PGC-1α seems to be important for the induction of thermogenic genes in BAT on cold exposure, whereas PGC-1β may regulate basal mitochondrial gene expression or compensate for loss of PGC-1α (39)(40)(41). Subcutaneous IWAT was found to be the most sensitive adipose tissue to this loss of PGC-1α.…”
Section: Discussionsupporting
confidence: 80%
“…Similar data have been reported from cultures of brown adipocytes isolated from whole-body PGC-1α knockout mice (39). PGC-1α seems to be important for the induction of thermogenic genes in BAT on cold exposure, whereas PGC-1β may regulate basal mitochondrial gene expression or compensate for loss of PGC-1α (39)(40)(41). Subcutaneous IWAT was found to be the most sensitive adipose tissue to this loss of PGC-1α.…”
Section: Discussionsupporting
confidence: 80%
“…We observed that overexpression of Pgc-1β was able to drive a transcriptional programme that increased the capacity for mitochondrial substrate oxidation, improved antioxidant defences and partially protected against HFD-induced insulin resistance. Gain-and loss-of-function studies have shown that PGC-1β regulates the expression of genes involved in mitochondrial function and lipid metabolism [15,16,38,39]. However, although much is known about the physiological stimuli that increase PGC-1α content in muscle, the in vivo regulation of PGC-1β is less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…They increase mitochondrial energy production by inducing the expression of genes that regulate fatty acid oxidation and by increasing mitochondrial activity (Kamei et al, 2003;Lin et al, 2003;Meirhaeghe et al, 2003;St-Pierre et al, 2003). Moreover, mice lacking either PGC-1a or PGC-1b exhibit little to no effect on mitochondrial mass and respiration activity (Lin et al, 2004;Leone et al, 2005;Lelliott et al, 2006;Sonoda et al, 2007). However, RNAimediated down-regulation of PGC-1b in PGC-1a À/À preadipocyte lines additively inhibits mitochondrial respiration (Uldry et al, 2006).…”
Section: Introductionmentioning
confidence: 99%